Implementing PROFIT syntax for authentic financial literacy writing instruction - Yani Andriyani Gustina; Yeti Mulyati; Vismaia S. Damaianti; Andoyo Sastromiharjo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study examines the implementation of the PROFIT (Problem Orientation, Reflection, Organization, Facilitation, Interaction, Transformation) syntax, developed from the Authentic Learning Experiences model with Financial Literacy content (ALE-LF), in vocational writing instruction. The ALE-LF model supports real-life, experience-based learning relevant to vocational students, particularly in connecting writing skills with financial contexts. Using a Research and Development (R&D) approach, the study involved preliminary research, prototype development, and assessment phases with 32 eleventh-grade students and two Indonesian language teachers at SMK Sinar Parahyangan. Financial literacy was integrated through observation report writing based on simple financial projects, with teachers acting as facilitators and reflective partners. The model was validated by vocational education academics and practitioners. Challenges included teachers’ adaptation to project-based approaches and time limitations. The PROFIT syntax was most effective during the Organization, Interaction, and Transformation stages, improving writing structure, idea cohesion, and reflective expression. The model is pedagogically feasible, though findings are limited to similar vocational contexts.